Etude de l’effet du pH de milieu réactionnel sur les propriétés des nanoparticules d’oxyde métallique obtenue par méthode verte - GHERBI, Bachir (Universty Of El-oued جامعة الوادي, 2024)
This study explores an eco-friendly approach to synthesizing zinc oxide (ZnO) nanoparticles using plant extracts as an alternative to conventional physical or chemical methods. ZnO nanoparticles were produced via a green synthesis process using Portulaca oleracea (purslane) leaf extract at varying pH levels of 4, 6, 9.5, and 11. The impact of pH on the optical and structural characteristics of the synthesized nanoparticles was investigated. Ultraviolet-visible (UV-Vis) spectrophotometry and Fourier-transform infrared (FTIR) spectroscopy techniques were employed to analyze the optical properties, while scanning electron microscopy (SEM) and X-ray diffraction (XRD) were utilized to study the structural properties. Additionally, the photocatalytic performance of the synthesized ZnO nanoparticles was evaluated through the degradation of methyl orange dye. The characterization results confirmed the successful biosynthesis of ZnO nanoparticles with sizes ranging from 22.17 to 27.38 nm. UV-Vis analysis revealed maximum absorption in the 350-380 nm range, indicative of the Zn-O bond. FTIR spectra exhibited a distinct peak at 474 cm-1, attributed to Zn-O vibrations. SEM images revealed that the obtained nanoparticles generally exhibited spherical or oval morphologies. The synthesis pH significantly influenced the optical and morphological properties of the ZnO nanoparticles. The results demonstrated the high performance of the green-synthesized ZnO nanoparticles in dye degradation applications. يعد التوليف الأخضر لجسيمات أكسيد المعدن النانوية من المستخلصات النباتية بديلاً واعداً للطريقة التقليدية للتوليف الفيزيائي أو الكيميائي. في هذه الدراسة، تم تصنيع جسيمات أكسيد الزنك النانوية (NPs) باستخدام التخليق الأخضر عند قيم أس هيدروجيني مختلفة هي 4، 6، 9.5، و11 عن طريق مستخلص أوراق رجلة، وتمت دراسة تأثير الرقم الهيدروجيني على الخصائص البصرية والتركيبية. تم تشخيص الخواص البصرية باستخدام مقاييس الطيف الضوئي UV-Vis، كما تم تشخيص الخواص البصرية بواسطة التحليل الطيفي FTIR. وفي الوقت نفسه، تم تشخيص الخصائص الهيكلية باستخدام المجهر الإلكتروني الماسح (SEM) وحيود الأشعة السينية (XRD). علاوة على ذلك، تم فحص تحلل صبغتها الضوئية مقابل صبغة الميثيل البرتقالية. أكدت نتائج التوصيف نجاح التخليق الحيوي لجسيمات أكسيد الزنك النانوية ذات حجم يتراوح بين 22.17 إلى 27.38 نانومتر. يُظهر تحليل الأشعة فوق البنفسجية (UV-Vis) أقصى امتصاص في النطاق 350-380 نانومتر ينتمي إلى Zn-O. تُظهر أطياف FT-IR ذروة مميزة عند 474 سم-1، والتي تعزى إلى اهتزاز Zn-O. تظهر صورة المجهر الإلكتروني الماسح (SEM) أن الجسيمات النانوية التي تم الحصول عليها عادة ما تكون كروية أو بيضاوية. أثرت قيمة الرقم الهيدروجيني التخليقي بشكل كبير على الخصائص البصرية والمورفولوجية لـ ZnO NPs. أشارت النتائج أيضًا إلى الأداء العالي لمركبات ZnO NPs المركبة بالتخليق الأخضر لتدهور الصبغة.
أطروحة دكتوراه تخصص: هندسة كيميائية في العلوم التكنولوجيا
Keywords: Bio-synthesis; Portulaca oleracea; Zinc oxide NPs; nanoparticles; Photodegradation; Methyl orange; Sustainability; التخليق الأخضر، رجلة، أكسيد الزنك، الجسيمات النانوية المعدنية، التحفيز الضوئي، ميثيل برتقالي، الاستدامة